THE ASSOCIATIONS OF LEISURE ACTIVITY AND HEALTH AMONG KOREAN BABY BOOMERS. (11th November 2018) - Choi, B; Jun, H
Abstract: As the baby boomers are facing retirement and empty nest, life planning in their old age are gaining increasing importance. This study aims to analyze the associations between leisure activity and health (subjective health and life satisfaction) among baby boomers in Korea. The sample is 1, 629 baby boomers (53 to 59 years old) from the Korean Longitudinal Study of Aging in 2014. Participation in five types of activities such as travel/sightseeing/picnic (travel), seeing movies/performances/exhibitions/sports (seeing), hobby/entertainment-related gatherings (hobby), education/entertainment programs (programs), volunteering were put in the model. Among these, travel and hobby was positively associated with life satisfaction. Travel, hobby and volunteering were positively associated with subjective health. This study suggests that some types of leisure activity can have positive impact on the health of baby boomers. However, given the low levels of overall participation, social and policy efforts to promote ongoing participation in these activities are needed.